Effects of 15 weeks of resistance exercise on pro-inflammatory cytokine levels in the vastus lateralis muscle of patients with fibromyalgia. Issue 1 (December 2016) - Ernberg, Malin; Christidis, Nikolaos; Ghafouri, Bijar; Bileviciute-Ljungar, Indre; Löfgren, Monika; Larsson, Anette; Palstam, Annie; Bjersing, Jan; Mannerkorpi, Kaisa; Kosek, Eva; Gerdle, Björn
Abstract Background This study aimed at investigating the effect of a resistance exercise intervention on the interstitial muscle levels of pro-inflammatory cytokines in fibromyalgia (FMS) and healthy controls (CON). Methods Twenty-four female patients with FMS (54 ± 8 years) and 27 female CON (54 ± 9 years) were subjected to intramuscular microdialysis of the most painful vastus lateralis muscle before and after 15 weeks of progressive resistance exercise twice per week. Baseline dialysates were sampled in the resting muscle 140 min after insertion of the microdialysis catheter. The participants then performed repetitive dynamic contractions (knee extension) for 20 min, followed by 60 min rest. Pain intensity was assessed with a 0–100 mm visual analogue scale (VAS), and fatigue was assessed with Borg's RPE throughout microdialysis. Dialysates were sampled every 20 min and analyzed with Luminex for interleukin (IL)-1β, tumor necrosis factor (TNF) alpha, IL-6, and IL-8. Results At both sessions and for both groups the dynamic contractions increased pain (P  < 0.012) and fatigue (P  < 0.001). The levels of TNF were lower in the FMS group than the CON group at both sessions (P  < 0.05), but none of the other cytokines differed between the groups. IL-6 and IL-8 increased after the dynamic contractions in both groups (P  < 0.010), while TNF increased only in CON (P  < 0.05) and IL-1β did not change. Overall pain intensity was reduced after the 15 weeks of resistance exercise in FMS (P  < 0.05), but there was no changes in fatigue or cytokine levels. Conclusion Progressive resistance exercise for 15 weeks did not affect the interstitial levels of IL-1β, TNF, IL-6, and IL-8 in the vastus lateralis muscle of FMS patients or CON. Trial registration Clinicaltrials.govNCT01226784, registered 21 October 2010.